Analysis on Civil Servants’ Competence Development Program to Enhance The Performance of The Department of Tourism, Culture, Youth and Sports in Sumedang Regency (Institut Pemerintahan Dalam Negeri, 2023)
The growth and development of human resources are crucial in the era of globalization, as competent personnel are needed to effectively navigate the challenges of the global landscape. This is particularly important in regions with tourism potential, where competent Civil Servants are necessary to drive and advance the tourism sector. This research evaluated the competency development of the Department of Tourism, Culture, Youth and Sports in Sumedang Regency, West Java. Factors that inhibited the competency growth were also identified along with possible attempts to overcome these obstacles. Qualitative descriptive method and inductive approach were employed, and the data were collected through interviews, observations, and documentation. The data analysis process involved parameter reduction, presentation, verification, and drawing conclusions based on the research findings. The findings indicate that the Tourism, Culture, Youth and Sports Office of Sumedang Regency has made progress in the development of civil servants competency. However, various challenges persisted, such as limited funds allocated for the development process and the lack of interest among the Civil Servants to actively engage. To address these obstacles, the Office of Tourism, Culture, Youth and Sports is collaborating with other agencies and actively participating in civil servant webinars.ABSTRAK Sumber daya manusia harus tumbuh dan berkembang untuk tampil di tingkat yang lebih tinggi dalam periode globalisasi. Ini menunjukkan perlunya perangkat daerah dengan kemampuan membawa otoritas yang kuat. Salah satu daerah di Jawa Barat yang memiliki potensi wisata dimana dibutuhkan aparatur yang kompeten untuk menangani dan memajukan sektor pariwisata. Oleh karena itu, penelitian ini bertujuan untuk mengevaluasi pertumbuhan kompetensi perangkat Dinas Pariwisata Kebudayaan Kepemudaan Dan Olah Raga Kabupaten Sumedang Jawa Barat. berusaha untuk mengidentifikasi hambatan yang relevan dan upaya yang dilakukan untuk melewatinya. Teknik Pengumpulan Data Dalam penelitian ini, wawancara, observasi, dan dokumentasi digunakan untuk mengumpulkan data dengan menggunakan metode deskriptif kualitatif dan pendekatan induktif. Selain itu, reduksi parameter, presentasi, verifikasi, dan kesimpulan digunakan dalam proses analisis data. Berdasarkan hasil penelitian ditemuan tersebut, Dinas Pariwisata Kebudayaan Kepemudaan dan Olah Raga Kabupaten Sumedang berhasil melaksanakan pengembangan kompetensi aparatur. Meskipun demikian, berbagai kesulitan masih terlihat, seperti keterbatasan dana untuk proses pembangunan dan ketidaktertarikan aparatur untuk bertindak. Dinas Pariwisata Kebudayaan Kepemudaan dan Olah Raga bekerja sama dengan dinas lain untuk mengatasi kendala tersebut dan berpartisipasi dalam webinar aparatur.